CHARACTERISTICS OF MALONG (Muraenesox cinereus) AND KEMBUNG (Rastrelliger brachysoma) AS SURIMI RAW MATERIAL - Andri Nofreeana; Untung Trimo Laksono (Journal of Aquaculture Development and Environment, 2022)
The use of fish as raw material for surimi continued to grow along with the increasing demand for surimi-based processed products. The fish used from marine fish to freshwater fish. The use of fresh fish as raw material greatly affected the quality of surimi. The morphological characteristics of fish raw materials affected the yield of fish meat, this can be seen in the yield of each fish. This research used two types of fish, namely Malong / Daggertooth pike conger fish (Muraenesox cinereus) and Kembung / Mackerel fish (Rastrelliger brachysoma). In general, the results of the proximate test showed that the protein levels in the fish used were not significant. Malong fish was very potential to be used as raw material for surimi because it produced the highest yield, which was 66.67% with 62.44% myofibril and 25.6% sarcoplasm. Kembung/Mackerel fish in this study resulted in the lowest yield of 37.00% with 59.69% of myofibril and 46.6% of sarcoplasm. Gel formation in surimi was strongly influenced by myofibril and sarcoplasmic proteins. Gel formation in fish meat was strongly influenced by the presence of salt-soluble proteins in the form of myofibrils (actin and myosin). On the other hand, if fish meat contained more water-soluble protein (sarcoplasm), it would be relatively reduce its gel formation ability.